Old Ways of Drawing and Thinking: The Currency of ‘Character’ - Baalman, Dirk (DASH | Delft Architectural Studies on Housing, 2018)
In the spring of 2011, new street lamps were installed in Deventer’s protected townscape. As in other places, the public lighting is modern and consists of LEDs. That said, Deventer chose to fit them in replica nineteenth-century lamps. The city paradoxically chose a 150-year-old fitting for the most advanced twenty-first-century technology. Deventer appears to have so little faith in its twenty-first-century creative industry that it has resorted to that of the nineteenth century. Not so a few years ago when the manhole covers in the city centre were replaced and the chosen design was a subtle cast-iron one that brought the rich tradition of casting iron into the present. Now an old drawing appears to be favoured over and above a new one and there seems to be no desire to add to the cultural tradition: what was is better than what might be. Oddly enough the fittings have branches for the lamplighter’s ladder (although the last lamplighter retired some 80 years ago). And another paradoxical side-effect: the railway and road bridges over the IJssel in Deventer were bombed during the Second World War; the adjacent neighbourhoods were rebuilt in the 1950s. The current set-up creates the impression that the nineteenth-century streetlamps miraculously survived those bombardments.